Associational decomposition: After‐life traits and interactions among decomposing litters control during‐life aggregation of plant species. (19th July 2020) - Barbe, Lou; Mony, Cendrine; Jung, Vincent; Uroy, Léa; Prinzing, Andreas
Abstract: While species may coexist at population level, their individuals may still segregate, at least temporarily, and hence interact little. Aggregation among heterospecific individuals may require particular during‐life traits, for example, traits limiting competition for space or resources. But is aggregation also facilitated by after‐life traits accelerating decomposition of plant litters, notably through synergy among co‐decomposing litters? We investigated the role of leaf traits, litter traits and litter‐mixture decomposition in the spatial aggregation of individuals of pairs of grassland species in a long‐term mesocosm experiment. We related aggregation between pairs of species to mean and dissimilarity in (a) during‐life traits related to resource‐acquisition and clonal dispersal, (b) after‐life traits related to decomposition and (c) rate and synergy of decomposition. In most years, aggregation of heterospecific individuals strongly increased with means of (a) during‐life clonal traits reducing competition for space, and (b) after‐life traits increasing litter decomposition. Trait dissimilarities had comparatively less influence. Interestingly, in the last year, synergistic decomposition among litters improved species aggregation. Overall, after‐life interactions due to fast and synergistic decomposition appear to increase during‐life aggregation between individuals of different plant species. We introduce the concept of 'associational decomposition', equivalent to associational resistance, but mediated via decomposers rather than enemies. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article .